Effects of Product Quality, Service Quality, Price Perception, and Reputation on Purchase Intention: The Mediating and Moderating Roles of Trust in Shopee as an Online Shopping E-Commerce - Atika Ayu Listari; Arif Hartono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research entitled "Effects of Product Quality, Service Quality, Price Perception, and Reputation on Purchase Intention: The Mediating and Moderating Roles of Trust in Shopee as an Online Shopping E-Commerce" aims to examine and analyze the influence of the shopping experience based on product quality, service quality, price perception, reputation, and consumer confidence in purchase intentions on the Shopee application. The method used in this research is an online questionnaire via Google Form with a sampling technique of 220 respondents and using Structural Equation Modeling data analysis with the help of AMOS 23 software. Based on the data analysis carried out, it was concluded that product quality, service quality, price perception, reputation, and increased consumer confidence in E-Commerce has a positive influence on consumers' purchase intentions.